Motor learning changes the axon initial segment of the spinal motoneuron. - Wang, Yu; Chen, Yi; Chen, Lu; Herron, Bruce J; Chen, Xiang Yang; Wolpaw, Jonathan R (J Physiol, 2024)
We are studying the mechanisms of H-reflex operant conditioning, a simple form of learning. Modelling studies in the literature and our previous data suggested that changes in the axon initial segment (AIS) might contribute. To explore this, we used blinded quantitative histological and immunohistochemical methods to study in adult rats the impact of H-reflex conditioning on the AIS of the spinal motoneuron that produces the reflex. Successful, but not unsuccessful, H-reflex up-conditioning was associated with greater AIS length and distance from soma; greater length correlated with greater H-reflex increase. Modelling studies in the literature suggest that these increases may increase motoneuron excitability, supporting the hypothesis that they may contribute to H-reflex increase. Up-conditioning did not affect AIS ankyrin G (AnkG) immunoreactivity (IR), p-p38 protein kinase IR, or GABAergic terminals. Successful, but not unsuccessful, H-reflex down-conditioning was associated with more GABAergic terminals on the AIS, weaker AnkG-IR, and stronger p-p38-IR. More GABAergic terminals and weaker AnkG-IR correlated with greater H-reflex decrease. These changes might potentially contribute to the positive shift in motoneuron firing threshold underlying H-reflex decrease; they are consistent with modelling suggesting that sodium channel change may be responsible. H-reflex down-conditioning did not affect AIS dimensions. This evidence that AIS plasticity is associated with and might contribute to H-reflex conditioning adds to evidence that motor learning involves both spinal and brain plasticity, and both neuronal and synaptic plasticity. AIS properties of spinal motoneurons are likely to reflect the combined influence of all the motor skills that share these motoneurons. KEY POINTS: Neuronal action potentials normally begin in the axon initial segment (AIS). AIS plasticity affects neuronal excitability in development and disease. Whether it does so in learning is unknown. Operant conditioning of a spinal reflex, a simple learning model, changes the rat spinal motoneuron AIS. Successful, but not unsuccessful, H-reflex up-conditioning is associated with greater AIS length and distance from soma. Successful, but not unsuccessful, down-conditioning is associated with more AIS GABAergic terminals, less ankyrin G, and more p-p38 protein kinase. The associations between AIS plasticity and successful H-reflex conditioning are consistent with those between AIS plasticity and functional changes in development and disease, and with those predicted by modelling studies in the literature. Motor learning changes neurons and synapses in spinal cord and brain. Because spinal motoneurons are the final common pathway for behaviour, their AIS properties probably reflect the combined impact of all the behaviours that use these motoneurons.
Keywords: Animals; Ankyrins; Axon Initial Segment; Axons; Conditioning, Operant; H-Reflex; Learning; Male; Motor Neurons; Neuronal Plasticity; Rats; Rats, Sprague-Dawley; Spinal Cord

Why New Spinal Cord Plasticity Does Not Disrupt Old Motor Behaviors - Chen, Yi; Chen, Lu; Wang, Yu; Chen, Xiang Yang; Jonathan Wolpaw (The Journal of Neuroscience, 2017)
When new motor learning changes the spinal cord, old behaviors are not impaired; their key features are preserved by additional compensatory plasticity. To explore the mechanisms responsible for this compensatory plasticity, we transected the spinal dorsal ascending tract before or after female rats acquired a new behavior—operantly conditioned increase or decrease in the right soleus H-reflex—and examined an old behavior—locomotion. Neither spinal dorsal ascending tract transection nor H-reflex conditioning alone impaired locomotion. Nevertheless, when spinal dorsal ascending tract transection and H-reflex conditioning were combined, the rats developed a limp and a tilted posture that correlated in direction and magnitude with the H-reflex change. When the right H-reflex was increased by conditioning, the right step lasted longer than the left and the right hip was higher than the left; when the right H-reflex was decreased by conditioning, the opposite occurred. These results indicate that ascending sensory input guides the compensatory plasticity that normally prevents the plasticity underlying H-reflex change from impairing locomotion. They support the concept of the state of the spinal cord as a negotiated equilibrium that reflects the concurrent influences of all the behaviors in an individual's repertoire; and they support the new therapeutic strategies this concept introduces.
Keywords: H-Reflex; motor learning; operant conditioning; plasticity; Rehabilitation; Spinal Cord

Ablation of the inferior olive prevents H-reflex down-conditioning in rats. - Xiang Yang Chen; Wang, Yu; Yi Chen; Chen, Lu; Jonathan Wolpaw (Journal of neurophysiology, 2016)
We evaluated the role of the inferior olive (IO) in acquisition of the spinal cord plasticity that underlies H-reflex down-conditioning, a simple motor skill. The IO was chemically ablated before a 50-day exposure to an operant conditioning protocol that rewarded a smaller soleus H-reflex. In normal rats, down-conditioning succeeds (i.e., H-reflex size decreases at least 20%) in 80% of animals. Down-conditioning failed in every IO-ablated rat (P< 0.001 vs. normal rats). IO ablation itself had no long-term effect on H-reflex size. These results indicate that the IO is essential for acquisition of a down-conditioned H-reflex. With previous data, they support the hypothesis that IO and cortical inputs to cerebellum enable the cerebellum to guide sensorimotor cortex plasticity that produces and maintains the spinal cord plasticity that underlies the down-conditioned H-reflex. They help to further define H-reflex conditioning as a model for understanding motor learning and as a new approach to enhancing functional recovery after trauma or disease.
Keywords: Spinal Cord

Cortical stimulation causes long-term changes in H-reflexes and spinal motoneuron GABA receptors. - Wang, Yu; Yi Chen; Lu Chen; Jonathan Wolpaw; Xiang Yang Chen (Journal of neurophysiology, 2012)
The cortex gradually modifies the spinal cord during development, throughout later life, and in response to trauma or disease. The mechanisms of this essential function are not well understood. In this study, weak electrical stimulation of rat sensorimotor cortex increased the soleus H-reflex, increased the numbers and sizes of GABAergic spinal interneurons and GABAergic terminals on soleus motoneurons, and decreased GABA(A) and GABA(B) receptor labeling in these motoneurons. Several months after the stimulation ended the interneuron and terminal increases had disappeared, but the H-reflex increase and the receptor decreases remained. The changes in GABAergic terminals and GABA(B) receptors accurately predicted the changes in H-reflex size. The results reveal a new long-term dimension to cortical-spinal interactions and raise new therapeutic possibilities.
Keywords: Spinal Cord

H-reflex up-conditioning encourages recovery of EMG activity and H-reflexes after sciatic nerve transection and repair in rats. - Yi Chen; Wang, Yu; Lu Chen; Sun, Chenyou; English, Arthur W.; Jonathan Wolpaw; Xiang Yang Chen (The Journal of neuroscience : the official journal of the Society for Neuroscience, 2010)
Operant conditioning of the spinal stretch reflex or its electrical analog, the H-reflex, produces spinal cord plasticity and can thereby affect motoneuron responses to primary afferent input. To explore whether this conditioning can affect the functional outcome after peripheral nerve injury, we assessed the effect of up-conditioning soleus (SOL) H-reflex on SOL and tibialis anterior (TA) function after sciatic nerve transection and repair. Sprague Dawley rats were implanted with EMG electrodes in SOL and TA and stimulating cuffs on the posterior tibial nerve. After control data collection, the sciatic nerve was transected and repaired and the rat was exposed for 120 d to continued control data collection (TC rats) or SOL H-reflex up-conditioning (TU rats). At the end of data collection, motoneurons that had reinnervated SOL and TA were labeled retrogradely. Putative primary afferent terminals [i.e., terminals containing vesicular glutamate transporter-1 (VGLUT1)] on SOL motoneurons were studied immunohistochemically. SOL (and probably TA) background EMG activity recovered faster in TU rats than in TC rats, and the final recovered SOL H-reflex was significantly larger in TU than in TC rats. TU and TC rats had significantly fewer labeled motoneurons and higher proportions of double-labeled motoneurons than untransected rats. VGLUT1 terminals were significantly more numerous on SOL motoneurons of TU than TC rats. Combined with the larger H-reflexes in TU rats, this anatomical finding supports the hypothesis that SOL H-reflex up-conditioning strengthened primary afferent reinnervation of SOL motoneurons. These results suggest that H-reflex up-conditioning may improve functional recovery after nerve injury and repair.
Keywords: conditioning; peripheral nerve; plasticity; Reflex; regeneration; Spinal Cord

H-reflex down-conditioning greatly increases the number of identifiable GABAergic interneurons in rat ventral horn. - Wang, Yu; Pillai, Shreejith; Jonathan Wolpaw; Xiang Yang Chen (Neuroscience letters, 2009)
H-reflex down-conditioning increases GABAergic terminals on spinal cord motoneurons. To explore the origins of these terminals, we studied the numbers and distributions of spinal cord GABAergic interneurons. The number of identifiable GABAergic interneurons in the ventral horn was 78% greater in rats in which down-conditioning was successful than in naive rats or rats in which down-conditioning failed. No increase occurred in other spinal lamina or on the contralateral side. This finding supports the hypothesis that the corticospinal tract influence that induces the motoneuron plasticity underlying down-conditioning reaches the motoneuron through GABAergic interneurons in the ventral horn.
Keywords: activity-dependent plasticity; GABAergic interneurons; H-reflex conditioning; learning and memory; Motor control; Spinal Cord

Effects of H-reflex up-conditioning on GABAergic terminals on rat soleus motoneurons. - Pillai, Shreejith; Wang, Yu; Jonathan Wolpaw; Xiang Yang Chen (The European journal of neuroscience, 2008)
To explore the role of spinal cord plasticity in motor learning, we evaluated the effects of H-reflex operant conditioning on GABAergic input to rat spinal motoneurons. Previous work indicated that down-conditioning of soleus H-reflex increases GABAergic input to soleus motoneurons. This study explored the effect of H-reflex up-conditioning on GABAergic input. Of nine rats exposed to H-reflex up-conditioning, up-conditioning was successful (H-reflex increase >or= 20%) in seven and failed (change < 20%) in two. These rats and eight naive control (i.e. unconditioned) rats were injected with cholera toxin subunit B-conjugated Alexa fluor 488 into the soleus muscle to retrogradely label soleus motoneurons. Sections containing soleus motoneurons were processed for GAD(67) [one of the two principal forms of the GABA-synthesizing enzyme glutamic acid decarboxylase (GAD)] with an ABC-peroxidase system. Two blinded independent raters counted and measured GABAergic terminals on these motoneurons. Unlike successful down-conditioning, which greatly increased the number of identifiable GABAergic terminals on the motoneurons, up-conditioning did not significantly change GABAergic terminal number. Successful up-conditioning did produce slight but statistically significant increases in GABAergic terminal diameter and soma coverage. These results are consistent with other data indicating that up- and down-conditioning are not mirror images of each other, but rather have different mechanisms. Although the marked changes in GABAergic terminals with down-conditioning probably contribute to H-reflex decrease, the modest changes in GABAergic terminals associated with up-conditioning may be compensatory or reactive plasticity, rather than the plasticity responsible for H-reflex increase. As a variety of spinal and supraspinal GABAergic neurons innervate motoneurons, the changes found with up-conditioning may be in terminals other than those affected in successful down-conditioning.
Keywords: activity-dependent plasticity; Learning; Memory; Motor control; Spinal Cord

Motor learning changes GABAergic terminals on spinal motoneurons in normal rats. - Wang, Yu; Pillai, Shreejith; Jonathan Wolpaw; Xiang Yang Chen (The European journal of neuroscience, 2006)
The role of spinal cord plasticity in motor learning is largely unknown. This study explored the effects of H-reflex operant conditioning, a simple model of motor learning, on GABAergic input to spinal motoneurons in rats. Soleus motoneurons were labeled by retrograde transport of a fluorescent tracer and GABAergic terminals on them were identified by glutamic acid decarboxylase (GAD)67 immunoreactivity. Three groups were studied: (i) rats in which down-conditioning had reduced the H-reflex (successful HRdown rats); (ii) rats in which down-conditioning had not reduced the H-reflex (unsuccessful HRdown rats) and (iii) unconditioned (naive) rats. The number, size and GAD density of GABAergic terminals, and their coverage of the motoneuron, were significantly greater in successful HRdown rats than in unsuccessful HRdown or naive rats. It is likely that these differences are due to modifications in terminals from spinal interneurons in lamina VI-VII and that the increased terminal number, size, GAD density and coverage in successful HRdown rats reflect and convey a corticospinal tract influence that changes motoneuron firing threshold and thereby decreases the H-reflex. GABAergic terminals in spinal cord change after spinal cord transection. The present results demonstrate that such spinal cord plasticity also occurs in intact rats in the course of motor learning and suggest that this plasticity contributes to skill acquisition.
Keywords: activity-dependent plasticity; GABA; H-Reflex; Memory; Motor control; Spinal Cord